Slow-Wave Sleep Is Associated With Incident Hypertension: The Sleep Heart Health Study. Issue 1 (26th October 2017) - Javaheri, Sogol; Zhao, Ying Y; Punjabi, Naresh M; Quan, Stuart F; Gottlieb, Daniel J; Redline, Susan
Abstract: We sought to quantify the association between slow-wave (stage N3) sleep and hypertension in a large cohort of middle-aged men and women. Data from 1850 participants free of baseline hypertension from the Sleep Heart Health Study were analyzed. The primary exposure was percentage of N3 sleep on baseline in-home polysomnography and the primary outcome was incident hypertension, defined as systolic blood pressure ≥ 140 mm Hg, diastolic blood pressure ≥ 90 mm Hg, and/or use of any blood pressure lowering medications at follow-up. Multivariable logistic regression models were adjusted for study site, age, sex, race, waist circumference, tobacco use, alcohol use, apnea–hypopnea index, nocturnal oxygen desaturation, sleep duration, sleep efficiency, and arousal index. Mean age was 59.4 ± 10.1 years and 55.5% were female. The mean baseline systolic and diastolic blood pressure was 118.8 and 70.6 mm Hg, respectively. Approximately 30% of the sample developed hypertension during a mean follow-up of 5.3 years. In the multi-adjusted model, participants in quartiles 1 (<9.8%) and 2 (9.8%–17.7%) of N3 sleep had significantly greater odds of incident hypertension compared with those in quartile 3 (17.7%–25.2%) (OR 1.69, 95% CI 1.21–2.36, p = .002 and OR 1.45, 95% CI 1.04–2.00, p = .03, respectively). No significant effect modification by sex on the N3-hypertension association was observed. In conclusion, compared with intermediate levels of N3 sleep (overlapping the "normal" adult range), lower levels of percent N3 sleep are associated with increased odds of incident hypertension in both men and women, independent of potential confounders, including indices of sleep apnea and sleep fragmentation.